ANALISIS PENGGUNAAN KAYU BAKAR MASYARAKAT DI DUSUN SALENA KELURAHAN BULURI KECAMATAN ULUJADI KOTA PALU - Jumadil, .; Rachman, Imran; Hapid, Abdul (Jurnal Warta Rimba, 2018)
Until now, timber is still the most important fuel especially for rural communities. Firewood for nearby forest communities is an indispensable source of energy to meet daily kitchen needs, and is an additional source of income to meet their daily needs. The increasing consumption of firewood is a serious problem. If the problem is not sought the appropriate way out, it will interfere with the existence of the forest. Therefore, it is necessary to study the needs of firewood in Salena hamlet for the benefit of forest development. This study aims to determine the level of use of firewood In Salena Hamlet Village Buluri District Ulujadi Palu City. This research was conducted from April to May 2017, located at Dusun Salena Buluri Urban District Ulujadi Palu City. The method used in this research is survey and interview to the respondents as much as 26 families or 15% of 176 families. Based on the observation of firewood which dikosumsi by 176 KK is equal to 1244,32 kg / kk per day or 2.07 m3. The average firewood rate per month for each respondent is 37329.6 kg / kk or 62.19 m3, and the average annual firewood rate for each respondent is 447955.2 kg / kk or 746.34 m3. The wood species used are acacia wood (Acacia denticulosa), marantaipa wood (Mangifera foetida L) and Lamtoro wood (Leucaena leucocephala).Keywords: Usage Analysis, firewood, village Salena